2020
DOI: 10.1002/mds.28143
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Deregulation in Blood Serum Identifies Multiple System Atrophy Altered Pathways

Abstract: methamphetamine can reduce BK channel surface expression in dopaminergic neurons, 20 amphetamine likely exerts its effect through the dopamine system to curb the patient's dystonia spells. Future studies are needed to uncover the neurological mechanism of dextroamphetamine in controlling such spells and examine whether administration of stimulants could be a general therapeutic option to treat other KCNMA1-linked channelopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…We found salivary miR-29a-3p has adequate specificity for differentiating idiopathic PD from MSA and ET. Previous studies indicated that serum miRNA-7641 and miRNA-191 could differentiate MSA from PD, and that plasma miR-4639-5p had adequate sensitivity and specificity to discriminate between PD and ET patients (8,9). Despite these recognized limitations of diagnostic accuracy, salivary miRNA has promising diagnostic value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found salivary miR-29a-3p has adequate specificity for differentiating idiopathic PD from MSA and ET. Previous studies indicated that serum miRNA-7641 and miRNA-191 could differentiate MSA from PD, and that plasma miR-4639-5p had adequate sensitivity and specificity to discriminate between PD and ET patients (8,9). Despite these recognized limitations of diagnostic accuracy, salivary miRNA has promising diagnostic value.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have evaluated the disease specificity of miRNAs among PD, MSA and ET. Serum miR-7641, miR-191 and plasma miR-19b-3p may be useful for differentiating PD and multiple system atrophy (MSA) (7,8). Plasma hsa-miR-4639-5p may discriminate between PD patients and ET patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…We used two endogenous and one exogenous miRNA simultaneously for normalization in all RT‐qPCR comparisons 17,18 . As endogenous normalizers, we selected hsa‐miR‐320a‐3p and hsa‐miR‐6727‐5p among the most stable miRNAs from the array across all samples as identified using the NormFinder software 19 in other α‐synucleinopathies studies in our population, i.e., MSA 20 and LRRK2‐associated PD (Marta Soto, Manel Fernández, Paloma Bravo, Alicia Garrido, Antonio Sánchez‐Rodríguez, María Rivera‐Sánchez, María Sierra, Paula Melón, Anna Naito, Bradford Casey, Eduardo Tolosa, María‐José Martí, Jon Infante, Mario Ezquerra and Rubén Fernández‐Santiago). As an exogenous normalizer, we used the Caenorhabditis elegans miRNA cel‐miR‐39‐3p added to all serum samples at a final concentration of 5 pM 18 .…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of ferritin heavy chains is dependent on the release of free iron and cytoplasmic iron efflux when the membrane transport protein Fe-ATPase is activated, leading to a decrease in intracellular free Fe 2+ content and preventing the occurrence of Fentonian iron death-induced cell damage (Götz et al, 2004). Mitochondrial RNA (mtRNA) may alter iron death by regulating the expression of Nrf2 (Pérez-Soriano et al, 2020), where different isoforms have different regulation of Nrf2, inducing activation of Nrf2 pathway through inhibition of Keap1 or increasing the aggregation of Nrf2 in the nucleus through Cullin-3 (Cul3). Heme oxygenase (HO) is a protective factor, metabolite with Fe2+ production, and its Nrf2/HO-1 pathway can regulate intracellular iron concentration (LIP).…”
Section: Nrf2 and Iron Deathmentioning
confidence: 99%